Online monitoring of dyskinesia in patients with Parkinson's disease. - Keijsers, N.L.W.
Discusses utilizing wearable movement sensors to successfully detect and assess severity of Parkinsonion symptoms in daily life. The authors describe the present state-of-the-art of online monitoring of motor behavior. They focus on modern monitoring equipment and on new analysis tools, which allow a quantitative detection and assessment of dyskinesias throughout the day, by an objective, unsupervised rating of dyskinesias using clinical rating scores.
Keywords: Parkinsonion symptoms severity assessment; Analysis tools; Clinical rating scores; Dyskinesias; Medical instrumentation; Modern monitoring equipment; Motor behavior; Objective unsupervised rating; State-of-the-art online monitoring; Wearable movement sensors